Dose Variation To Critical Points In Low Dose Rate Intracavitary Brachytherapy Of Cervical Cancer As Justification For Incident Learning - Addison, Eric C.D.K.; Adom, Joseph; Hasford, Francis; Amuasi, John H. (European Scientific Journal, ESJ, 2022)
Background: Low Dose Rate (LDR) brachytherapy necessitates a more extended treatment duration. This technique maintains the patient on the treatment machine for a longer length of time, which may cause changes in the applicators’ position due to vaginal packing soaking and patient movement for incident learning justification. Objective: The purpose of this study is to evaluate pre- and post-dosage variation to points ’A’ and ’B,’ as well as vital organs (i.e. bladder and rectum), for low dose rate (LDR) brachytherapy at Komfo Anokye Teaching Hospital and justify the need for incident learning system. Method: Forty (40) patients with invasive cervical cancer were treated with LDR brachytherapy equipment (A Curietron Cesium Manuel (AMRA)-France, CA 98.22) to point ’A’ at doses ranging from 30 to 35 Gy. Adult patients selected for the study ranged from 25 to 60 years simulated. For each patient, orthogonal images of anterior-posterior (AP) and (LAT) were taken by positioning the patient on the Varian Acuity Simulator Couch at 00 and 900, respectively, and two sets of orthogonal images (before and after treatment), in each case, were considered. The treatment was then planned using the AP and LAT images obtained based on the four arrangements used, namely 1-2-5, 1-3-5, 1-4-5, and 1-5. The treatment planning system used for the study was the Prowess Panther system 4.6. Results: The dosage disparity at point ’A’ was determined to be 1.16 per cent, which is highly commendable compared to previous research that established dose variations of 2%, 35%, 8%, and 20%. In this study, the dosage variation at point B was 0.75 per cent. The bladder and rectum had average alterations of 2.32 per cent and 0.30 per cent, respectively. Conclusion: The difference observed between prescribed, and deposited dosage was 2.11 per cent for quality assurance and incident learning reasons. Unrealistic expectations, reliance on reminders and quick remedies, and faults in the systemic view of failure were discovered and addressed as managerial issues. It is critical not to underestimate these difficulties because they are frequently significantly more severe than the technical issues being addressed. Incident issues were not recorded per patients under review, but near misses and non-conformance were observed. The geometric variances between the Intracavitary Brachytherapy Treatment (ICBT) applicators and the essential organs change during the treatment process, resulting in dosage changes. Does variance is within the required standard limits; it can be stated that Komfo Anokye Teaching Hospital’s practice satisfies the international standard and is an intrusion into the Directorate Incident Learning System.